USING WATER INDICES (NDWI, MNDWI, NDMI, WRI AND AWEI) TO DETECT PHYSICAL AND CHEMICAL PARAMETERS BY APPLY REMOTE SENSING AND GIS TECHNIQUES - Mustafa, Mustafa T.; Hassoon, Khalid I.; Hussain, Hussain M.; Abd, Modher H. (International Journal of Research -GRANTHAALAYAH, 2017)
This study was undertaken by analyzing data from satellite image (Landsat-8 OLI) and geographical information system (GIS) to find the relationship between water parameters and water indices of spectral images. The main purpose of this research was to develop a model for the physical and chemical parameters of Gharraf stream in Iraq. The water parameters used in this study included: acidity (PH), Total Dissolved Solids (T.D.S), Alkalinity(ALK), Electrical Conductivity (E.C), Calcium(Ca), Chloride (CL), Sodium (Na), Sulfate (SO4), Potassium (k), Total suspended solid (T.S.S), Total Hardness (TH).Where the samples were taken to seventeen stations with two seasons and at the same time took a satellite image on 4/FEB, 11 / MAY.GIS techniques were used in the beginning to project the coordinates of seventeen stations along the stream in Landsat-8 satellite image for extract data. Then, these data are treated in SPSS software for purpose finding correlation and regression equations. Positive strong correlations between the reflectance of the satellite image and the water parameters in 4/FEB and 11/ MAY with five stations, helped to build six regression models. These models could be used to predict these six water parameters (PH, E.c, CL, SO4, Na and K) at any point along the stream in Iraq from the satellite image directly.